ANALISIS LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PEGADAIAN (PERSERO) CABANG JIMBARAN - PUSPITA, YUANDA; SANJAYA, SUKA; WINAYA, TERISTIYANI (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted to analyze the physical work environment and non-physical work environment on employee performance at PT. Pegadaian (Persero) Jimbaran Branch. Aims to find out the influence of the physical work environment and non-physical work environment on employee performance. The population in the study were all employees at PT. Pegadaian (Persero) Jimbaran Branch numbered 40 people and were asked to fill out a 6-point Likert scale questionnaire containing 31 statements. Data analysis techniques use descriptive statistical analysis, correlation analysis, multiple linear analysis, determination tests and hypothesis tests. The results of data analysis show the physical work environment at PT. Pegadaian (Persero) Jimbaran Branch has a positive and significant influence on employee performance, seen from the results of the t test with a significance value of 0.000. Meanwhile, the non-physical work environment also has a positive and significant effect on employee performance as seen from the results of the t test with a significance value of 0.001. The physical work environment and non-physical work environment have a simultaneous influence as seen from the results of the F test with a significance value of F of 0.000.